Integrated platform for operating and interrogating organs-on-chips. Issue 43 (23rd October 2019) - Ishahak, Matthew; Birman, Liev; Carbonero, Daniel; Hill, Jordan; Hernandez, Adiel; Rawal, Siddarth; Agarwal, Ashutosh
Abstract : Microfluidic platform and open-source graphical user interface automates continuous dynamic culture and assessment of organs-on-chips. Abstract : The development of microphysiological systems, also known as organs-on-chips, has highlighted the need for improved in vitro models for drug discovery. However, the highly specialized skillset required to design, build, and operate these systems has hindered adoption. Here, we describe an integrated platform that enables both continuous perifusion culture and dynamic cell secretion assays. We also developed a graphical user interface that allows the user to not only control the hardware components, but also define automated programs. The system's functionality was validated by maintaining pancreatic islets in culture under continuous perifusion for 24 hours, then performing a functional glucose stimulated insulin secretion assay. We demonstrate that islets remained both viable and functional on the platform with minimal user involvement.